2022
DOI: 10.3389/fmed.2022.882763
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Signature Consisting of Pyroptosis-Related Genes and SCAF11 for Predicting Immune Response in Breast Cancer

Abstract: Pyroptosis, characterized as an inflammasome-mediated cell death pathway, may be participated in tumorigenesis and progression. However, the underlying molecular function and mechanism of pyroptosis in BRCA remain unclear. In our study, we aimed to develop a prognostic signature in BRCA based on pyroptosis-associated genes. Data was downloaded from TCGA database, and then we screened 760 female BRCA samples and 104 normal breast tissues as the training set. Seven pyroptosis-related genes (CASP9, GPX4, IL18, NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, the AUCs of the signatures at 3-, 5-, and 10-year were 0.683, 0.640, and 0.794, respectively, significantly higher than most hallmark predictive models. Table 1 showed that the 3-, 5-, and 10-year AUCs of the other four prognostic signatures, namely, the 9 ferroptosis-related gene signature (3-, 5-, and 10-year AUCs: 0.713, 0.713, and 0.684) ( Lu et al, 2022a ), 4 immune-related gene signature (3-, 5-, and 10-year AUCs: 0.692, 0.691, and 0.715) ( Ding et al, 2021 ), 7 pyroptosis-related gene signature (3-, 5-, and 10-year AUCs: 0.785, 0.769, and 0.711) ( Chu et al, 2022 ), and 6 autophagy-related gene signature (3-, 5-, and 10-year AUCs: 0.640, 0.600, and 0.610) ( Zhong et al, 2020 ) were comparable to the predictive capabilities of our predictive model, and our signature stand out with a clear advantage in predicting the long-term survival of BC patients, with a 10-year AUC of 0.819. We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival.…”
Section: Resultsmentioning
confidence: 99%
“…SCAF11, also known as caspase-11, is a pro-in ammatory enzyme, which may have a role in cancer-associated angiogenesis [51]. Chu et al demonstrated that knocking down SCAF11 suppressed cell proliferation and colony formation in breast cancer cell lines [52].…”
Section: Discussionmentioning
confidence: 99%
“…XianTao aims to provide users with a better understanding of gene interpretation, and enrichment results to the researcher (https://www.xiantao.love) [48][49][50]. In this study, we get several enrichment pathways associated with the ALKBH family in breast cancer disease from the database.…”
Section: Xiantaomentioning
confidence: 99%